The Effect of Pairwise Video Feedback on the Learning of Elegant Eye-Hand Coordination Skill - Majid Arab; Seyed Mehdi Dastfal; Ehsan Zareian (The Society of Aging and Physical Activity (SAPA), 2014)
The present paper aimed to study the effect of pairwise video check feedback (including the observation of external pattern of skill performance and performing the skill simultaneously) on the learning on acquisition and learning of eye-hand coordination skill. Computer skill of eye-hand coordination skill was the tool used in this study. 24 subjects were randomly selected and equally divided into two groups of experimental and control. Each of the groups performed 3 exercise sessions of 5 attempts with a 24-hour interval between sessions. In each exercise attempt, the experimental group conducted a combination of pairwise video feedback and practical performance of the skill and the control group only performed the practical exercises. Acquisition tests were done at the end of training sessions and retention tests were performed after intervals of 24 hours, 48 hours, and one week after the last session of acquisition. Performing the task in lesser time was the criteria for assessment of individuals. The results showed a significant improvement in the performance of task from the pretest to the final stage of acquisition. Also, over time (24 hours, 48 hours, and after the last training session) in retention test, a stability in performance was seen. Finally, it was found that pairwise video feedback method positively affect the acquisition of skill and retention stability of individuals in eye-hand coordination skill.